2002
DOI: 10.1097/00004728-200201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Tomography of Interpulmonary Saddle Embolism: Extent and Vascular Distribution

Abstract: Interpulmonary saddle emboli appear to be a transient form of acute pulmonary embolism, the site of predilection for rupture of the embolus being the level of the bifurcation. Their frequency may therefore be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
0
23
0
4
Order By: Relevance
“…Radiological evidence of SE is found in approximately 2-5% of all patients with PE [7,8]. However, its true frequency may be underestimated because many patients are too unstable to undergo CT angiography (CTA), and the diagnosis is often established at autopsy.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Radiological evidence of SE is found in approximately 2-5% of all patients with PE [7,8]. However, its true frequency may be underestimated because many patients are too unstable to undergo CT angiography (CTA), and the diagnosis is often established at autopsy.…”
Section: Advances In Knowledgementioning
confidence: 99%
“…However, the true incidence is difficult to determine since many patients are too unstable to receive a CT angiogram (CTA) and the diagnosis is often established at autopsy. Some have proposed that SPE represents a transient form of acute PE, thus their true frequency may therefore be understimated (6). Saddle PE represents a large clot burden and is an important risk for right ventricular dysfunction and sudden hemodynamic collapse.…”
Section: Introductionmentioning
confidence: 99%
“…A saddle embolism is characterised by an embolus that extends across the bifurcation of a vessel for example the main pulmonary artery, the distal aorta, or even a patent foramen ovale. 1 Serial studies have reported cardiac disease in 90% of patients with peripheral arterial embolism or saddle embolus, particularly ischaemic heart disease, valvular disorders or atrial fibrillation. 2 The cauda equina, and rarely the conus medullaris, are supplied by the lower lumbar, iliolumbar and lateral sacral arteries.…”
Section: Discussionmentioning
confidence: 99%